Implementation of the Incremental Model in Developing Android Educational Applications for Children with Intellectual Disabilities - Neonbeni, Firman Yosef Rangga; Rema, Yasinta Oktaviana Legu; Risald, Risald; Manek, Patricia Gertrudis; Manek, Siprianus Septian (Program Studi Pendidikan Teknologi Infromasi UMK, 2026)
Learning for children with intellectual disabilities requires adaptive and engaging instructional media, particularly within the context of inclusive education. However, learning activities at SLB Bhakti Luhur Atambua still face challenges due to the limited number of educators and the use of conventional teaching methods, creating a need for more interactive learning media. This study aims to develop an Android-based educational application named KenaliKu as an interactive learning medium to introduce body parts, colors, and facial expressions. This research employed a Research and Development (R&D) approach using the Incremental model, which includes requirement analysis, system design, coding, testing, and final release stages. System evaluation was conducted through Black Box Testing and User Acceptance Testing (UAT). Black Box Testing was performed by three experts in the field of Information Technology to evaluate system functionality, while User Acceptance Testing (UAT) involved 18 respondents consisting of students, teachers, and parents. The results of Black Box Testing indicate that all system functions operated according to the specified requirements, while User Acceptance Testing (UAT) obtained an average score of 96.18%, categorized as very good. These findings indicate that KenaliKu was successfully developed using the Incremental model and is functionally feasible as an educational application for children with intellectual disabilities. The high UAT score demonstrates positive user acceptance, while the application provides an interactive and user-friendly learning environment that has the potential to support the learning process and inclusive education practices.